The qir?'a adopted by the authors of Tafs?r al-Jal?layn and its significance in understanding their exegetical notes - Hoosen, F. (Journal for semitics, 2011)
The Tafs?r al-Jal?layn, by virtue of its conciseness, is one of the most commonly taught books of Qur?'nic exegesis in Islamic institutions around the world. It features prominently in the curriculum of nearly all Islamic seminaries in South Africa, India, Pakistan, Malaysia, Nigeria and other countries. By virtue of its popularity the Tafs?r has received a great deal of attention from scholars and publishers alike. As a result there are many editions of the work available today. In addition there are many scholars who have authored marginal notes on the commentary itself, both in Arabic (Ahmad al-Ṣawi and Sulayman al-Jamal for instance) and Urdu (for example Muḥammad Naeem). In recent times the Tafs?r al-Jal?layn has also been translated into English. (The translations of Feras Hamza and Aisha Bewley are two examples.) The style of commentary adopted by the authors of Jal?layn is to expand the Qur?'nic text by embedding explicatory remarks within the verses. It is on account of this that in nearly all available editions of the work the commentary of the authors is situated alongside the text of the Qur?'n. However the text of the Qur?'n generally used is that of the popular reading of Ḣafṣ ibn Sulayman al-Asadi from Aṣim ibn Abi al-Najud, the reading found in most printed versions of the Qur?'n today. On account of this, it is not immediately evident how the commentary of Jal?layn fits with the associated verse of the Qur?'n. Some contemporary writers have gone to great lengths of interpretation in their attempts to explain these apparent inconsistencies. The solution is a simpler one: the question of variant qir?'a (Qur?'nic reading). This article, by means of textual analysis of the commentary in comparison to the Qur?'nic text accompanied by external evidence, attempts to show that the authors of Jal?layn based their commentary on a reading other than that of Ḣafṣ from Aṣim, a fact that is often missed. It further attempts to demonstrate that Jal?layn was most probably based largely on the reading of Abu'Amr Zabban ibn 'Ala'al-Baṣri (d. 154/733) thus offering a solution to the problem of inconsistency between the commentary and the text in most instances.